Relationship between Self Concepts and Students' Academic Achievements in Selected Medical Colleges (Bangladesh Journal of Medical Education, 2014)
This cross - sectional descriptive study was conducted to explore the relationship of medical students' self-concept with their academic achievement. The study population was preclinical second year medical students. Study was carried out at one government and one non-government medical colleges in Dhaka. Sample size was 254 and sampling technique was purposive. The three dimensions of self concept: personal, family and social self-concept of medical students were assessed through 45- items questionnaire, which was answered on a five-point Likert scale. Data was collected by self administered structured questionnaire with Bengali version. Academic achievement data were measured by two term examinations marks of three subjects (Anatomy, Physiology & Biochemistry) based on written and oral examinations. Simple statistical tests were used to analyze the dominant dimension of student's self-concept. Inferential statistic such as ttest was used to analyze the difference between the self-concept and gender. Pearson correlations were used analyze the relationship between self-concept of students with their academic achievement. The participant's age ranged from 17 - 23 years with a mean of 19.8 and a standard deviation of 0.93. Among the respondents 47% were male and 53% were females. In term-I and term-II exams majority (66.9% and 66.1%) student were high achievers. The research finding showed that the dominant dimension of self concept was family self-concept (mean value was 53.73). Beside that, t-test analysis showed that there was significant difference between dimension of self-concept of students according to gender (p= 0.03, p= 0.02). Pearson correlations analysis showed that there was positive correlation between dimensions of self-concept with student's academic achievement. Study recommended to increase the student's self-concept in order to enhance their academic achievement. DOI: http://dx.doi.org/10.3329/bjme.v2i1.18131 Bangladesh Journal of Medical Education Vol.2(1) 2011: 10-13